Does Oil Price Uncertainty Transmit to Stock Markets? - Martin Ågren (Uppsala University, Department of Economics, 2006)
The paper presents an empirical study of volatility spillover from oil prices to stock markets within an asymmetric BEKK model. Using weekly data on the aggregate stock markets of Japan, Norway, Sweden, the U.K., and the U.S., strong evidence of volatility spillover is found for all stock markets but the Swedish one, where only weak evidence is found. News impact surfaces show that, although statistically significant, the volatility spillovers are quantitatively small. The stock markets own shocks, which are related to other factors of uncertainty than the oil price, are more prominent than oil shocks.
urn:nbn:se:uu:diva-83258
Keywords: C32; G10; 330; Volatility spillover; multivariate GARCH; BEKK; oil shocks; stock market; Ölpreis; Aktienmarkt; Spillover-Effekt; Ökonometrisches Modell